Kandungan Bahan Kering, NDF Dan ADF Silase Pakan Komplit menggunakan Buangan Sayuran Pasar - Syahruddin Syahruddin (Gorontalo Journal of Equatorial Animals, 2023)
ABSTRACTThis study aims to know the contents of dry matter, NDF (Neutral Detergents Fiber), and ADF (Acid Detergent Fiber) in complete feed silage using market vegetable waste as a substitute for gamal leaves. This study uses completely randomized design (CRD) with 5 treatments and 4 replications. The treatment consists of P1: 35% natural grass + 40% gamal leaves + 0% market vegetable waste + 25% concentrate; P2: 35% natural grass + 30% gamal leaves + 10% market vegetable waste + 25% concentrate; P3: 35% natural grass + 20% gamal leaves + 20% market vegetables waste + 25% concentrate; P4: 35% natural grass + 10% gamal leaves + 30% market vegetable waste + 25% concentrate; P5: 35% natural grass + 0% gamal leaves + 40% market vegetables waste + 25% concentrate. Parameters measured are the contents of dry matter, NDF, and ADF in complete feed silage. The finding shows the treatments P3, P4 and P5 significantly (P0,01) reduce the content of dry matter compared to treatments P1 and P2. The treatments P4 significantly (P0,01) reduces the contents of NDF in complete feed silage compared to treatments P1, P2 and P3. Thus, it can be concluded that the use of 30% market vegetable waste as a substitute for gamal leaves can reduce the contents of dry matter, NDF, and ADF in complete feed silage. Market vegetable waste can substitute up to 30% of the use of gamal leaves. Keywords: market vegetable waste; NDF (Neutral Detergent Fiber); ADF (Acid Detergent Fiber), complete feed silage.